2018
DOI: 10.3846/20294913.2016.1216905
|View full text |Cite
|
Sign up to set email alerts
|

Multiattribute Evaluation of Organic and Inorganic Agricultural Food Investments Using Fuzzy Topsis

Abstract: Since people well know the threats of inorganic agriculture to their health, they are more interested in organic agriculture than ever. Organic agriculture is expected to play a major role for a healthy world in the future whereas inorganic agriculture nowadays increases the volume of agricultural production and presents lower priced foods but causes health problems. The agricultural investments are generally evaluated by using linguistic terms since most of the evaluation criteria are intangible and inherentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The usability of TOPSIS continues to motivate researchers of information and decision making sciences to further develop the method by novel approaches (Shen et al, 2018). It has been demonstrated that improved and extended versions of TOPSIS can tackle more complex problems than can conventional TOPSIS (Shouzhen andYao, 2018, Suder andKahraman, 2018).…”
Section: Brief Review Of Recent Developments In Topsismentioning
confidence: 99%
“…The usability of TOPSIS continues to motivate researchers of information and decision making sciences to further develop the method by novel approaches (Shen et al, 2018). It has been demonstrated that improved and extended versions of TOPSIS can tackle more complex problems than can conventional TOPSIS (Shouzhen andYao, 2018, Suder andKahraman, 2018).…”
Section: Brief Review Of Recent Developments In Topsismentioning
confidence: 99%
“…Organic farming requires maximum level of natural soil while inorganic farming can use minimum level natural soil and increase the growth of plants using chemicals. Suder and Kahraman (2018) solved the problem of organic and inorganic farming using TOPSIS method under fuzzy logic rankings. We have taken some part of data from Suder and Kahraman (2018) and edited the data to discuss uncertainty in farming decisions under rough environment.…”
Section: Organic and Inorganic Agricultural Food Investmentmentioning
confidence: 99%
“…Suder and Kahraman (2018) solved the problem of organic and inorganic farming using TOPSIS method under fuzzy logic rankings. We have taken some part of data from Suder and Kahraman (2018) and edited the data to discuss uncertainty in farming decisions under rough environment. The evaluations of the experts for each alternative under given criteria is given in Table 11 and the weights of experts for all criteria are given in Table 12.…”
Section: Organic and Inorganic Agricultural Food Investmentmentioning
confidence: 99%
“…The TOPSIS method has a number of advantages (Selim et al, 2016;Suder & Kahraman, 2018;Xue et al, 2008;Zolfani et al, 2012):…”
Section: Introductionmentioning
confidence: 99%